2014
DOI: 10.1002/mame.201400245
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Reduced Graphite Oxide and Mechanochemically Functionalized Graphene as Functional Fillers for Epoxy Nanocomposites

Abstract: In this study we examine graphene with different shape, size, functionality and electrical conductivity as carbon nanofiller for epoxy (EP) composites. Thermally reduced graphite oxide (TRGO) and a nitrogen doped derivative (N-TRGO) are compared with multilayer graphene (MLG) derived from milling of graphite. Whereas wet grinding of graphite forms stable non-functionalized MLG dispersions, solvent free dry grinding of graphite under N 2 and CO 2 pressure allows for mechanochemical functionalization of graphite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…an increase of 13.4 %). Tschoppe et al (2015) report an increase in the modulus of 8.5 % for an epoxy composite filled with 1.5 wt% of thermally reduced GO and 11.4 % for that filled with 2 wt% of nitrogen-doped thermally reduced GO, whereas Zaman et al (2011) observed a modest 7 % increase in modulus on adding 2 wt% of 4,4 0 -methylene diphenyl diisocyanate (MDI)-functionalized GNP to epoxy. The increase in modulus observed in the present work may be ascribed to the relatively high modulus of the rGO filler and to the good interfacial adhesion between the rGO and the epoxy matrix.…”
Section: Thermo-mechanical Propertiesmentioning
confidence: 99%
“…an increase of 13.4 %). Tschoppe et al (2015) report an increase in the modulus of 8.5 % for an epoxy composite filled with 1.5 wt% of thermally reduced GO and 11.4 % for that filled with 2 wt% of nitrogen-doped thermally reduced GO, whereas Zaman et al (2011) observed a modest 7 % increase in modulus on adding 2 wt% of 4,4 0 -methylene diphenyl diisocyanate (MDI)-functionalized GNP to epoxy. The increase in modulus observed in the present work may be ascribed to the relatively high modulus of the rGO filler and to the good interfacial adhesion between the rGO and the epoxy matrix.…”
Section: Thermo-mechanical Propertiesmentioning
confidence: 99%
“…A detailed report about the synthesis procedure is presented by Tschoppe, et al [23]. Shortly, TRGO (thermally reduced graphite oxide) was synthesized by oxidation of graphite oxide and subsequent thermal reduction.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon‐based nanomaterials, including carbon nanotubes (CNTs), carbon nanohorns, and carbon nanocones/disks; and graphene and its derivations, such as graphene nanoplatelets (GNPs), porous graphene (NPG's), and graphene oxide (GO), are highly consumed as a means to modify the mechanical properties and toughness of epoxy‐based nanocomposites . Among nanocarbon materials, graphene, an atomic‐scale material with two‐dimensional (2D) honeycomb lattice and high‐specific surface area, has gained greater heed due to its magnificent properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among nanocarbon materials, graphene, an atomic‐scale material with two‐dimensional (2D) honeycomb lattice and high‐specific surface area, has gained greater heed due to its magnificent properties. Furthermore, it is worth mentioning that graphene is capable of fostering thermal and electrical properties of epoxy resin nanocomposites without hampering its stiffness (limiting its mechanical properties) . In our previous study, a synthetized porous graphene was added to epoxy matrices cured with four various hardeners in varying contents from 0 to 1 wt %.…”
Section: Introductionmentioning
confidence: 99%